The Influence of Personality Traits and Demographic Factors on Social Entrepreneurship Start Up Intentions - Koe Hwee Nga, Joyce (Journal of business ethics, 2010)
The sheer impact of the recent global financial turmoil and scandals (such as Enron and WorldCom) has demonstrated that unbridled commercial entrepreneurs who are allowed to pursue their short-term opportunities regardless of the consequences has led to a massive depreciation of the wealth of nations, social livelihood and environmental degradation. This article suggests that the time has come for entrepreneurs to adopt a more integrative view of business that blends economic, social and environmental values. Social entrepreneurs present such a proposition through their deep commitment towards the social vision, appreciation of sustainable practices, innovativeness, ability to build social networks and also generate viable financial returns. It could be expected that social entrepreneurs often possess certain distinct personality characteristics which define their behaviours/actions. Personality traits are partly developed by innate nurturing, socialization and education. These tacit traits are also formed values/beliefs held and play an important role in driving social entrepreneurial decision making. Thus, personality traits may influence the intentions and the manner in which the individual acts. We hold that if social entrepreneurship is to be effective and impactful, business and management education can facilitate the development of these critical personality traits. Thus, this study primes at determining the personality traits that influence social entrepreneurs’ start-up intentions. It also reinforces the findings that personality traits do influence entrepreneurship in general. This study examines the influence of the Big Five personality traits on social entrepreneurship dimensions. The findings reveal that agreeableness positively influences all dimensions of social entrepreneurship, whereas openness exerts a positive influence on social vision, innovation and financial returns. Methodologically, this study develops valid and reliable scales for social entrepreneurship and verifies the adopted Big Five personality measure of Schmit et al. (Pers Psychol 53:153–193, 2000) using the five-point Likert scale. The implication of this study is that element of appreciation of social responsibility, sustainability and character development needs to be integrated within the business education curriculum to support social entrepreneurs in realizing genuine value and impact to the causes and communities they serve. Future business leaders also need to be equipped with entrepreneurship skills, while exuding independent and reflective thinking in the pursuit life-long learning. The originality of this study lies in its focus on personality traits on social rather than commercial entrepreneurship. It is hoped that the findings will trigger a paradigm shift towards greater social entrepreneurship through education by nurturing sustainable development values in future business graduates.